Pengaruh Pengetahuan, Budaya Dan Dukungan Suami Terhadap Pengambilan Keputusan Alat Kontrasepsi: The Effect of Knowledge, Culture, and Husband's Support on Contraceptive Device Decision Making - hat, futi (Dohara POAJ, 2022)
Introduction: Family planning programs have a major impact on population growth, both quantitatively and qualitatively. Strengthening the use of contraceptives aims to reduce dropouts and prevent the increase in the incidence of unwanted pregnancies and the possibility of a